1996
DOI: 10.1126/science.271.5254.1393
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Dynamic Interaction of Vortices with Pinning Centers by Lorentz Microscopy

Abstract: When a magnetic field penetrates a superconductor, it forms lattices of thin filaments called magnetic vortices. If a current is applied, these vortices move if not pinned down, destroying the superconductivity. The spatiotemporal behavior of the vortices was observed in a niobium film with a square lattice of defects made by ion irradiation. The vortices formed a domain of lattices. When the intensity of the applied magnetic field was decreased, the vortices were driven out of the film across its edges; when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 7 publications
7
103
1
Order By: Relevance
“…This channel flow behavior has been observed experimentally using Lorentz microscopy [21]. Previous simulations of the coarse-grained BP model revealed results consistent with these and also showed that the channels can form a braided river which exhibit selfaffine (multifractal) behavior similar to fluvial braided rivers (see for example Ref.…”
Section: Some Comments On Conventional Theorysupporting
confidence: 66%
See 1 more Smart Citation
“…This channel flow behavior has been observed experimentally using Lorentz microscopy [21]. Previous simulations of the coarse-grained BP model revealed results consistent with these and also showed that the channels can form a braided river which exhibit selfaffine (multifractal) behavior similar to fluvial braided rivers (see for example Ref.…”
Section: Some Comments On Conventional Theorysupporting
confidence: 66%
“…These MD simulations do not, however, take into account a vortex density gradient, and do not agree with some the varieties of plastic dynamics observed in experiments. Section IV describes the original coarse-grained model, first used to describe vortex avalanches [4] and vortex rivers [19] as seen in experiments [20,21], and explains the exact model used here to describe the transport experiments summarized in Section II. To eliminate all potentially spurious sources of noise, a completely deterministic variant of the original BP model is used.…”
Section: A Summarymentioning
confidence: 99%
“…That vortex motion can strongly depend on local conditions was demonstrated in Ref. 23, where it was found that, in the presence of pinning, vortices move in a form of intermittent ''rivers'' between the pinned islands. In our case one can hardly discuss a motion around the pinned islands, since any important pinned fraction would affect the average transport properties significantly, which is not observed ͑see the discussion of Fig.…”
Section: B Noise In the Regime Of Linear V"i…mentioning
confidence: 99%
“…In particular, various imaging techniques [17,21,22] have established the existence of various states of driven vortices in conventional superconductors. However, for high-T c superconductors, almost nothing has been clarified, since these probes are applicable only over a limited parameter range (temperature, magnetic field, and driving force) [23][24][25]. For high-T c superconductors, we chose a slightly different approach; local-density-noise (LDN) measurement [26][27][28].…”
Section: Introductionmentioning
confidence: 99%